Upaya Hukum Banding Terhadap Tindak Pidana Memiliki Narkotika Golongan I - Kusnadi, Kusnadi; Hartanto, Hartanto; Marbun, Warasman (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the legal considerations of public prosecutors in filing appeals in narcotics cases with rehabilitation sentences. This normative-juridical study employs a legislative approach with descriptive analysis. In combating narcotics, Law Number 35 of 2009 serves as the primary legal reference. However, the application of minimum special fines presents challenges for judges, particularly due to the absence of regulatory mechanisms for their enforcement. This often renders fines inefficient. In this context, it is crucial for judges to deliver fair rulings by considering the offender's circumstances and the facts revealed during trials. The research findings indicate that prosecutors' appeals are often based on legal considerations requiring deeper exploration of trial facts. Additionally, the study finds that filing appeals against acquittals can be justified for the sake of legal certainty, justice, and utility. Appeal rulings from the Surabaya High Court (Number 83/Pid.Sus/2021/PT Sby.) and the Pontianak High Court (Number 69/Pid.Sus/2023/PT Ptk.) are based on strong legal grounds. The revised Article 29 of the Supreme Court Law emphasizes that defendants still have the right to file a second-level legal remedy, even if the prosecutors' grounds for appeal are deemed unjustifiable.